Study of metastasis in lymph node by fine needle aspiration cytology: our institutional experience - Patel, Mandakini M.; Italiya, Sonal L.; Dhandha, Zarana B.; Dudhat, Reena B.; Kaptan, Kumarbhargav R.; Shah, Mitesh B.; Mansuri, Benazeer M.; Thumar, Kazumi V.; Makwana, Gopal R. (International Journal of Research in Medical Sciences, 2017)
Background:Fine needle aspiration cytology (FNAC) is a reliable as well as an inexpensive diagnostic method. It is suitable for the developing countries for the diagnosis of lymphadenopathy at any approachable site. Fine needle aspiration cytology not only confirms the presence of metastatic disease but also, in most cases, gives the clue regarding the origin of the primary tumor, prognosis as well in the management of patient for staging purposes. The aim of the study was to detect and diagnose metastasis in lymph nodes. Methods:A study was done of all metastatic lymph node lesions reported in Department of Pathology, Govt. Medical College, Surat from May 2011 to April 2012. Results:A total of 2355 cases of fine needle aspiration cytology were carried out of which 580 cases were of lymph node. Cytology results were positive for metastasis in 157 specimens (27.06%). The most common site was cervical lymph nodes. Maximum numbers of cases of metastatic tumors were in 41-50 yrs age group. There were 115 males and 42 females with a male predominance (Male:Female= 2.8:1). The most common malignancy was squamous cells carcinoma, seen in 118 cases (75.15%), followed by metastatic mammary carcinoma (13 cases, 8.29%). In 26 cases out of 580 cases, histopathological confirmation was done and diagnostic accuracy of FNAC was 100%. Conclusions:Fine needle aspiration cytology of lymphadenopathy is a useful tool in diagnosing metastatic lesions with good certainty.